Neuronal control of peripheral insulin sensitivity and glucose metabolism - Johan Ruud (Nature Portfolio, 2017)
The brain controls peripheral glucose metabolism, for example by modulating hepatic gluconeogenesis or by regulating glucose uptake into brown adipose tissue. Here, the authors review the brain regions, neurons and molecular mechanisms involved in these processes, and discuss their relevance to disease.